PENINGKATAN EFISIENSI LAYANAN SEKOLAH DASAR NEGERI VIA REDESIGN PROSES ADMINISTRASI ORANG TUA SISWA - Jopinus Saragih; Hendri Mayanta; Rosmita Purba (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This Community Service Program (PKM) activity aims to improve the efficiency of administrative services for parents of students in public elementary schools through redesigning the main service processes (e.g., registration/re-registration, committee payments/contributions, processing of certificates, report card collection, transfer applications, and complaints). Common problems encountered were long waiting times during peak hours, inconsistent requirements information, repeated form completion, multiple approval flows, and difficult-to-track document archives. Interventions were carried out by mapping the as-is process, measuring service time, identifying waste, designing the to-be process (simplifying steps, standardizing forms, communication channels, and scheduling services), developing SOPs and document templates, and conducting implementation trials. Evaluation was carried out by comparing the KPIs before and after: waiting time, processing time, number of steps, error/rework rate, and parent satisfaction. The outputs were a new process map, service SOPs, a standardized form package, and a simple monitoring dashboard for sustainability.